Dommusikarchiv Salzburg (A-Sd) Thematischer Katalog der musikalischen Quellen, Reihe A - Neumayr, Eva (Hollitzer, 2018)
This is a catalogue of the musical sources of Salzburg Cathedral between ca. 1670 and 1841, that have survived in the holdings of the Dommusikarchiv at the Archiv der Erzdiözese Salzburg.